Can we talk about it? A qualitative study exploring occupational therapists' decision making in judging when to ask an older person about drinking alcohol. Issue 3 (3rd March 2022) - Maclean, Fiona; Dewing, Jan; Kantartzis, Sarah; Breckenridge, Jenna P.; McCormack, Brendan
Abstract: Older people now currently drink alcohol more frequently than previous generations, indicating a need to understand how this influences health and wellbeing in older adults. However, knowledge and awareness of the changing role alcohol plays in the lives of older people is not necessarily widely understood by allied health professionals in acute hospital contexts. In turn, conversations about drinking alcohol in later life may not be routinely addressed as part of practice, limiting an older person's choice to make informed decisions about their drinking. This paper qualitatively examines when occupational therapists (N = 17) in an acute hospital setting will initiate a conversation with older people (65+ years) about their drinking, guided by a theoretical lens that encompasses both person-centredness and collective occupation. Adopting a qualitative methodology, this study illustrates a typology of reasoning describing how, and in what circumstances, therapists ask older people about their alcohol use. Three themes were generated that provide further insight into the typology, these being 'hesitancy in practice', 'failure to link life transitions to alcohol use' and 'challenges of focusing on healthfulness'. These findings provide a potentially useful tool for therapists, services and organisations to self-assess their approach to asking older people about alcohol use; a necessary element of professional health-care practice as social trends in alcohol use continue to increase.